Práticas laboratoriais no ensino do jornalismo: o caso do Urbi@Orbi e os desafios da convergências mediática - Gradim, Anabela (2017)
Reflecting on the teaching of journalism in the current context of profound change in the journalistic field, affected by economic and political changes, technological changes, market changes, and new production processes, is the purpose of this work. Our departing point is a survey launched with current and former students of Communication Sciences at University of Beira Interior, where the practice of journalism in its online content innovation laboratory has been developing for more than 16 years. From this exploratory study we conclude that if journalism is to have a future, it will have to claim the reaffirmation of the field (Bourdieu); the professionalization of its agents (Schudson); the mastery of new technological tools; experimenting, as far as possible, with the tacit contracts governing the profession (Polanyi); and, mostly, it will have to preserve the specificity of journalism's values as a "discipline of veridiction" (Kovach & Rosenstiel).